Analisis Minat Masyarakat Surabaya Terhadap Udon (Kajian Sosiologi Budaya) - Nur Azizah; Eva Amalijah (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Abstract. The development of times and technology is increasingly rapid, facilitating the dissemination of information that makes foreign or foreign cultures enter a country. Especially the influence of foreign culture on food makes changes in the taste of foreign cuisine in Indonesian society. Like Japanese-style thick noodles or also called Udon, which are currently also found in many Japanese-style food outlets in Indonesia, especially in Surabaya. The purpose of this study is to describe the interest of the people of Surabaya in Udon. The method in this study uses a quantitative descriptive methode. A method that aims to create an objective picture or description of a research that uses numbers, starting from data collection, interpretation of the data as well as the appearance and results. Sample collection was carried out by distributing questionnaires in the form of online links to 150 respondents regarding the interest of the people of Surabaya in Udon. In this study using Likert scale analysis and Spearman rank correlation. The results obtained from the Likert scale data for the most preferred type of Udon are `Curry Udon` followed by `kake Udon` then `Nabeyaki Udon` with an interpretation rate of 53.16% which means that the respondent's interest in Udon is categorized as